Les « savoirs romantiques » de Daniel Fabre - Judith Lyon-Caen (L'Atelier du CRH)
Coming back to the project of history of the "anthropological perspective" proposed in the volume Savoirs romantiques (2011), directed by Jean-Marie Privat and Daniel Fabre, this article investigates how anthropological knowledge and writing according to Daniel Fabre are related to literature. While these links are usually thought as progressively separating, Fabre thought of them as constituently of "non separation"- and "indetermination"-types. In this paper, I show how interesting this idea of indetermination – of the "mixed" – can be, not only to grasp the anthropological gesture, as Fabre did, with a special focus on the "paradigm of the last" borrowed from De Martino, but also to deal with the status and uses of literature in the romantic moment, between science and poetry, between knowledge of otherness and intimate writing